Deepest far ultraviolet view of a central field in the Coma cluster by AstroSat UVIT - Mahajan, Smriti; Singh, Kulinder Pal; Pradeep, Kala G. (Cambridge University Press, 2022)
We present analysis of the far ultraviolet (FUV) emission of sources in the central region of the Coma cluster ( z=0.023 ) using the data taken by the UVIT aboard the multi-wavelength satellite mission AstroSat. We find a good correlation between the UVIT FUV flux and the fluxes in both wavebands of the Galex mission, for the common sources. We detect stars and galaxies, amongst which the brightest ( r≲17 mag) galaxies in the field of view are mostly members of the Coma cluster. We also detect three quasars ( z=0.38,0.51,2.31 ), one of which is likely the farthest object observed by the UVIT so far. In almost all the optical and UV colour-colour and colour-magnitude planes explored in this work, the Coma galaxies, other galaxies and bright stars could be separately identified, but the fainter stars and quasars often coincide with the faint galaxies. We have also investigated galaxies with unusual FUV morphology which are likely to be galaxies experiencing ram-pressure stripping in the cluster. Amongst others, two confirmed cluster members which were not investigated in the literature earlier, have been found to show unusual FUV emission. All the distorted sources are likely to have fallen into the cluster recently, and hence have not virialised yet. A subset of our data have optical spectroscopic information available from the archives. For these sources ( ∼10% of the sample), we find that 17 galaxies identify as star-forming, 18 as composite and 13 as host galaxies for active galactic nuclei, respectively on the emission-line diagnostic diagram.
Only IISER Mohali authors are available in the record.
Keywords: ultraviolet; field in the Coma